Words and numbers: a comparative study of medical and journalism students’ descriptors of risk, numeracy and preferences for health risk communication - Eleanor Fallon; Norma Bargary; Fergal Quinn; Aisling Leavy; Ailish Hannigan (BMC Medical Education, 2024)
Abstract Background Given the complementary roles of health professionals and journalists in communicating health risks to patients and the public, there have been calls for physicians to work with journalists to improve the quality of health information received by the public. Understanding the preferences of medical and journalism students for the way in which health risks are communicated and their understanding of words used to describe risk is an important first step to inform interdisciplinary learning. Methods Medical and journalism students (n = 203) completed an online survey where they were given qualitative descriptors of risk such as ‘a chance’, ‘probably’ and ‘unlikely’, and asked to assign a number that represents what the word means to them. Different formats of communicating risk (percentages, natural frequency and visual aids) were provided and students were asked to select and explain their preference. A thematic analysis of reasons was conducted. Numeracy and perceived mathematics ability were measured. Results Numbers assigned to the descriptor ‘A chance’ had the highest variability for medical students. Numbers assigned to the descriptor ‘Probably’ had the highest variability for journalism students. Using visual aids was the most popular format for risk communication for both courses (56% of medical students and 40% of journalism students). Using percentages was twice as popular with journalism students compared to medical students (36% vs. 18%). Perceived mathematics ability was lower in students with a preference for natural frequencies and in journalism students, however performance on an objective numeracy scale was similar for all three formats (percentages, natural frequency and visual aids). Reasons for choosing a preferred format included good communication, eliciting a response, or learning style. Conclusions Education on health risk communication for medical and journalism students should emphasize the need for qualitative descriptors of risk to be combined with the best available number. Students are already considering their role as future communicators of health risks and open to tailoring the mode of presentation to their audience. Further research is required on the design and evaluation of interdisciplinary workshops in health risk communication for medical and journalism students to maximise the opportunities for future inter-professional working.